Optimize the Supply Chain Problems Solving Features of Imperfect Quality Items Using EOQ Models Under Different Environment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper is “a supply chain problems comprising of supplier, manufacturer, and retailer have been thought of. Here supplier gets the crude materials in a ton and afterward the predominant quality items of the crude materials are sold at a more significant expense to the manufacturer after the screening the imperfect crude materials just as second-rate quality items of the crude materials are additionally offered to another manufacturer at a scaled down cost in a solitary cluster before the finish of penny percent screening process. A blend of great and imperfect quality items is created by the manufacturer. After some revise, some repairable bit of imperfect quality items is changed into immaculate quality items and some of non-repairable part of imperfect items are sold with marked down cost to the retailer. Retailer buys both great and imperfect quality items and offers the two items to the clients through his/her separate showrooms of limited limits at a commercial center. Here we utilized a diagnostic strategy and highlights of Supply Chain problems of imperfect items have been utilized to optimize the production rate and crude material request size for maximization of the normal benefit of the integrated model under various environments.” At long last, a numerical example is given to illustrate the model.